The impact of learning during the COVID-19 Pandemic on science literacy, social interaction, and digital literacy at Senior High School Palangkaraya City - Ikramina Yusti Amina; Herawati Susilo (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
The impact of COVID-19 on online learning biology 2020-2021 makes everyone panic, so it is necessary to be alert for innovation in learning, including in public high schools in Palangkaraya City. COVID-19 on social interactions that can affect psychosocial decline, digital literacy, the need for sorting educational information, and scientific literacy in the form of laboratory practicums do not exist because they have not found the right method. The purpose of the study is to describe three aspects that are affected by the pandemic, namely social interaction, scientific literacy, and digital literacy in online learning 2020 - now which is experiencing changes in lifestyle patterns. The type of research is qualitative phenomenological design, the method uses a questionnaire, semi-structured interview, and observation. The research was conducted in April 2022, totaling 58 people and one teacher and using purposive sampling data collection techniques. The data analysis technique used was three conditions and the stages of analysis consisted of data reduction with the help of NVivo-12, data presentation, and conclusion. The results show that COVID-19 with social interactions indicated a decline in students' psychosocial, digital literacy students are required to be able to, and scientific literacy that needs to be retrained because it is not optimal in assessing the performance process.AbstrakDampak COVID-19 pada pembelajaran online biologi 2020-2021 membuat kepanikan semua orang, sehingga perlu kesigapan inovasi dalam pembelajaran termasuk sekolah SMA Negeri di Kota Palangkaraya. COVID-19 terhadap interaksi sosial yang bisa mempengaruhi penurunan in psikososial, literasi digital perlunya pemilahan informasi pendidikan dan literasi sains dalam bentuk praktikum laboratorium tidak ada karena belum menemukan metode yang tepat. Tujuan penelitian mendeskripsikan tiga aspek yang dipengaruhi oleh pandemi yakni interaksi sosial, literasi sains, dan literasi digital pada pembelajaran online 2020 - sekarang yang mengalami perubahan pola gaya hidup. Jenis penelitian kualitatif desain fenomenologi, metode menggunakan kuesioner, wawancara semi struktur, dan observasi. Penelitian dilakukan April 2022, berjumlah 58 orang dan satu guru serta teknik pengambilan data purposive sampling. Teknik analisis data yang digunakan tiga kondisi dan tahapan analisis terdiri reduksi data dengan bantuan NVivo-12, penyajian data, dan menarik kesimpulan. Hasil menunjukkan COVID-19 dengan interaksi sosial yang diindikasi mengalami penurunan psikososial siswa, literasi digital siswa dituntut bisa, serta literasi sains yang perlu dilatih kembali karena kurang optimal dalam penilaian proses kinerja.